Near‐Field Photodetection in Direction Tunable Surface Plasmon Polaritons Waveguides Embedded with Graphene - Wu, Chia‐Hung; Ku, Chih‐Jen; Yu, Min‐Wen; Yang, Jhen‐Hong; Wu, Pei‐Yuan; Huang, Chen‐Bin; Lu, Tien‐Chang; Huang, Jer‐Shing; Ishii, Satoshi; Chen, Kuo‐Ping (Advanced science, 2023)
2D materials have manifested themselves as key components toward compact integrated circuits. Because of their capability to circumvent the diffraction limit, light manipulation using surface plasmon polaritons (SPPs) is highly‐valued. In this study, plasmonic photodetection using graphene as a 2D material is investigated. Non‐scattering near‐field detection of SPPs is implemented via monolayer graphene stacked under an SPP waveguide with a symmetric antenna. Energy conversion between radiation power and electrical signals is utilized for the photovoltaic and photoconductive processes of the gold‐graphene interface and biased electrodes, measuring a maximum photoresponsivity of 29.2 mA W −1 . The generated photocurrent is altered under the polarization state of the input light, producing a 400% contrast between the maximum and minimum signals. This result is universally applicable to all on‐chip optoelectronic circuits.